Geographical Information Systems (GIS) for Rural Development in Sub-Saharan Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Geographical Information Systems (GIS) for Rural Development in Sub-Saharan Africa